Perancangan Algoritma Sistem Kontrol Sekuensial pada Proses Mesin Pembuat Sirop Menggunakan PLC - Farhan, Muhammad Ghani; Rusli, Moch.; Siswojo, Bambang (Jurnal Mahasiswa TEUB, 2024)
The design of a Sequential Control System Algorithm for the Syrup Production Machine using PLC aims to enhance efficiency, accuracy, and consistency in production. In this research, the control algorithm is designed to automate various stages, including the transfer from truck to tank, heating, mixing of raw materials, and filling of the final product into packaging. Data collection was carried out through the simulation of a device created by the author, where sensors such as level, pressure, and temperature are integrated to detect operational conditions in real-time. The system then responds automatically to maintain product quality and minimize human error. The research results show that the designed system functions according to its capabilities, as demonstrated through checking the timeline diagram and validating against the truth table. The implementation of PLCbased control can improve production performance, reduce cycle time, and increase material filling accuracy while maintaining process stability and energy efficiency. Keywords: Sequential control system, PLC, syrup production, automation, production efficiency, simulation